The life relived in Discourse: analysis of english-learning experiences based on the notion of Perezhivanie and in the Appraisal System - Abreu, Diego Candido (The ESPecialist, 2025)
This paper has the main objective of producing understandings about the English learning experiences lived by an English learner based on the discursive reconstruction of these lived moments. In order to do so, the notion of perezhivanie (affective experience) gives theoretical foundation to the understanding about the role played by the affective experiences in the participant’s English learning pathway. A semistructured interview was produced with the goal of materializing in discourse these moments of the interviewee’s contact with the language. Aiming to have an analytical toolkit able to spot among the thread of experiences the discursive emerge of affectivity (entangled in the other haman psychological processes), this study uses the Appraisal System as a resource, understanding the appraisals as a privileged instance of manifestation of affects in language. The results point out a meaningful participation of the affective elements in the participant’s English learning route, besides giving evidence to teh relevant role played by appraisal in the discursive concretization of our affects.